The Whites : a novel - Brandt, Harry, 1949- (Henry Holt and Company, 2015)
"Back in the bad old days, when Billy Graves worked for an anti-crime unit in [the South Bronx] known as the Wild Geese, the NYPD branded him as a cowboy. Now forty, he has somehow survived and become a sergeant in Manhattan Night Watch. Mostly, his team of detectives conducts a series of holding actions--and after years in police purgatory, Billy is content simply to do his job. But soon after he gets a [4:00] a.m. call about the fatal knifing of a [man] in [Penn Station], his investigation moves beyond the usual handoff to the day shift. And when he discovers that the victim was once a suspect in the unsolved murder of a [12-year-old boy], he finds himself drawn back to the [mid]-1990s when the Wild Geese were at their most wayward"--